2004
DOI: 10.1111/j.1432-1033.2004.4142.x
|View full text |Cite
|
Sign up to set email alerts
|

The conformational stability of theStreptomyces coelicolorhistidine‐phosphocarrier protein

Abstract: Thermodynamic parameters describing the conformational stability of the histidine-containing phosphocarrier protein from Streptomyces coelicolor, scHPr, have been determined by steady-state fluorescence measurements of isothermal urea-denaturations, differential scanning calorimetry at different guanidinium hydrochloride concentrations and, independently, by far-UV circular dichroism measurements of isothermal urea-denaturations, and thermal denaturations at fixed urea concentrations. The equilibrium unfolding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 76 publications
(226 reference statements)
1
12
0
Order By: Relevance
“…The stability and the structure of the His-tagged protein are the same as those of the cleaved protein (10). Protein was purified as described (9).…”
Section: Purification Of Hpr Sc and Ei Scmentioning
confidence: 99%
See 1 more Smart Citation
“…The stability and the structure of the His-tagged protein are the same as those of the cleaved protein (10). Protein was purified as described (9).…”
Section: Purification Of Hpr Sc and Ei Scmentioning
confidence: 99%
“…There is a large homology between these PTS proteins and those of other antibiotic-resistant species, such as Vibrio cholerae and Streptococcus pneumoniae (3,7,8). We have undertaken an extensive description of the structures and conformational stabilities of the HPr sc and EI sc proteins (9)(10)(11)(12). HPr sc is a single polypeptide chain of 93 amino acids; it lacks cysteine and tyrosine residues, and it has one tryptophan and one phenylalanine.…”
Section: Introductionmentioning
confidence: 99%
“…We have undertaken an extensive description of the structures and conformational stabilities of the PTS proteins of S. coelicolor, first, to understand in depth the mechanism of the PTS; and, second, to provide new clues on the protein folding problem. For instance, we have shown that the thermodynamic folding parameters (DC p and m-values) of the HPr of S. coelicolor, HPr sc , are different from those of the other members of the HPr family (17)(18)(19). Interestingly enough, HPr sc , in contrast to the HPrs in Gram-negative bacteria and low-G1C Gram-positive bacteria (1), is not involved in general carbon regulation (20,21).…”
Section: Introductionmentioning
confidence: 97%
“…The presence of the different components of the PTS in S. coelicolor has been reported, and the corresponding proteins cloned and expressed [6,7]. We have undertaken an extensive description of the structures and conformational stabilities of the HPr and EI proteins in S. coelicolor [8][9][10][11]. HPr contains 93 amino acid residues; it lacks cysteine and tyrosine residues, and it only contains one tryptophan and one phenylalanine residues, close to the active site histidine.…”
Section: Introductionmentioning
confidence: 97%